2021
DOI: 10.1002/hep4.1704
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantifiable Predictors of Relapse in Patients with Alcohol‐Associated Liver Disease

Abstract: Abstinence in patients with alcohol-associated liver disease (ALD) reduces mortality. Most predictors of relapse are not quantifiable, preventing objective analysis of relapse risk and targeted intervention to improve clinical outcomes. We prospectively enrolled patients with ALD from November 2016 to December 2019 and administered a survey with two previously published scales to assess insight into alcohol-use disorder (Hanil Alcohol Insight Scale [HAIS]) and social support (Community Assessment Inventory Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…[23] It measures AAI in the non-LT ALD population [56][57][58] associating with alcohol relapse in unadjusted analysis (OR = 0.84 [0.72-0.97]), an association no longer significant after adjusted regression (OR = 0.70 [0.49-1.00]). [58] In non-ALD populations, insight measured by a modified HAIS correlated with the early success of outpatient SUD treatment. [59] HAIS-measured AAI interacted with a person's implicit alcohol preferences to predict alcohol relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] It measures AAI in the non-LT ALD population [56][57][58] associating with alcohol relapse in unadjusted analysis (OR = 0.84 [0.72-0.97]), an association no longer significant after adjusted regression (OR = 0.70 [0.49-1.00]). [58] In non-ALD populations, insight measured by a modified HAIS correlated with the early success of outpatient SUD treatment. [59] HAIS-measured AAI interacted with a person's implicit alcohol preferences to predict alcohol relapse.…”
Section: Discussionmentioning
confidence: 99%
“…The Hanil Alcohol Insight Scale (HAIS) is the most used AAI scale 23 . It measures AAI in the non-LT ALD population 56–58 associating with alcohol relapse in unadjusted analysis (OR = 0.84 [0.72–0.97]), an association no longer significant after adjusted regression (OR = 0.70 [0.49–1.00]) 58 . In non-ALD populations, insight measured by a modified HAIS correlated with the early success of outpatient SUD treatment 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study found the level of social support and level of adherence decreased in tandem with time elapsed from transplant [12 ▪ ], suggesting decreased social support may contribute to poorer adherence over time. Social support and alcohol relapse were also correlated, as patients who relapsed after transplant reported decreased social support within their home compared with patients who abstained posttransplant [13 ▪ ].…”
Section: Impact Of Social Support On Transplantationmentioning
confidence: 99%
“…Poor insight is strongly associated with avoidance of treatment (Probst et al, 2015), less successful quit attempts (Willems et al, 1973) and more premature dropouts (Ball et al, 2006) during treatment programs, less time of abstinence after discharge (Kim et al, 2007), and a higher risk of relapse (Dandaba et al, 2020, Shen et al, 2021.…”
Section: Introductionmentioning
confidence: 99%